DISKRESI HAKIM:POLA PENYELESAIAN KASUS DISPENSASI PERKAWINAN - Ramadhita, Ramadhita (Fakultas Syariah, 2014)
Underage marriage is still a problem for developing countries, including Indonesia. Various national and international research shows that the model has the potential marriage has increased in the decade ahead. In Indonesia, the marriage age limit set is 19 years for men and 16 years for women. Only, this limitation may file a dispensation remained unfulfilled by marriage to the religious court. The absence of standards in the Marriage Act opened the opportunity for the judges to make a decision based on its own initiative, which tends to refer to the textsÂ of fiqh. The implication, most requests are always granted dispensation, so that itÂ is as a causative factor of underage marriage.